Unveiling the burden of premenstrual dysphoric disorder: a narrative review to call for gender perspective and intersectional approaches - Islas-Preciado, Dannia; Ramos-Lira, Luciana; Estrada-Camarena, Erika (Frontiers in Psychiatry, 2025)
The present narrative review discusses the burden of Premenstrual Dysphoric Disorder (PMDD) and highlights the lack of awareness by analyzing the following key points: -Prevalence and Diagnosis: PMDD affects a significant portion of women during their reproductive years, but diagnosis is often delayed due to limited understanding and awareness. -Mental Health Burden: PMDD increases the risk of suicide attempts and negatively impacts quality of life. There are also economic costs associated with absenteeism and healthcare use. -Cultural and Gender Perspectives: Societal stigma surrounding menstruation and mental health likely contributes to underdiagnosis. -Lack of Sex and Gender Perspective in the Healthcare System: Research bias towards male subjects and historical neglect of women’s health issues contribute to limited knowledge about PMDD. -Non-Intersectional Approaches: Disparities in access to healthcare and the unique experiences of women further complicate PMDD diagnosis and treatment. -Vicious Cycle: The lack of research and awareness creates a vicious cycle where PMDD remains misunderstood and inaccurately treated. Finally, it emphasizes the need for increased awareness, education, and research on PMDD, particularly with a gendered and intersectional optic. The situation in Latin America is presented as a particular concern due to a lack of recent data and potentially higher prevalence due to socioeconomic factors.